Avanços e desafios na gestão municipal do SUS: um retrato das contratações de pessoas e serviços no estado de São Paulo - Kishima, Vanessa Sayuri Chaer (2012)
The role of cities and municipalities on guaranteeing health care supply in the field of Sistema Único de Saúde is ever-growing, making it increasingly necessary to rethink new alternatives for funding and supporting a more rational and efficient administration. This project has the goal of helping identify how such supplies are being guaranteed by local authorites, considering the budget restrictions imposed by staff expenses. The methodology carries out an exploratory first approach of local expenses, which has come to indicate impacts, the main one being an increase of third party expenses following the approval of Lei de Responsabilidade Fiscal. Based on that study, a spot-check on cities and municipalities in the State of São Paulo was developed, through interviews and information mappings regarding staff hiring and local services, both collected from local authorities, aiming to detect how health policies are being managed by their districts. The results come to point out the importance of investments that focus on regional inequalities and the questioning of why equal restrictions are assessed to realities which are totally unequal.